Gut microbiota and hypertension: a bibliometric analysis of recent research (2014–2023) - Jiao, Yang; Li, Wenxing; Zhang, Qianyi; Jiang, Qianfeng (Frontiers in Nutrition, 2023)
Background: Cardiovascular diseases persist as the primary cause of mortality in the global population. Hypertension (HTN) is widely recognized as one of the most crucial risk factors contributing to severe cardiovascular conditions. In recent years, a growing body of research has highlighted the therapeutic potential of gut microbiota (GM) in addressing cardiovascular diseases, particularly HTN. Consequently, unraveling and synthesizing the connections between GM and HTN, key research domains, and the underlying interaction mechanisms have grown increasingly vital. Methods: We retrieved articles related to GM and HTN from 2014 to 2023 using Web of Science. Bibliometric tools employed in this analysis include CiteSpace and VOSviewer. Results: From 2014 to 2023, we identified 1,730 related articles. These articles involved 88 countries (regions) and 9,573 authors. The articles were published in 593 journals, with 1000 references exhibiting co-occurrence more than ten times. The number of studies in this field has been increasing, indicating that it remains a research hotspot. We expect this field to continue gaining attention in the future. China leads in the number of published articles, while the United States boasts the most extensive international collaborations, signifying its continued prominence as a research hub in this domain. Tain You-Lin, Hsu Chien-Ning, Raizada Mohan K, and Yang Tao are among the authors with the highest publication volume. Publications in this field are frequently found in nutrition, cardiovascular, and molecular biology journals. The most frequently occurring keywords include metabolic syndrome, cardiovascular disease, inflammation, short-chain fatty acids, trimethylamine N-oxide, chronic kidney disease, heart failure, and high-salt diet. Conclusion: The relationship between GM and HTN is presently one of the most active research areas. By employing bibliometric tools, we analyzed critical and innovative articles in this field to provide an objective summary of the primary research directions, such as the relationship between GM and HTN, GM metabolites, high-salt diet, the developmental origins of health and disease, obstructive sleep apnea-Induced hypertension and antihypertensive peptide. Our analysis aims to offer researchers insights into hotspots and emerging trends in the field of GM and HTN for future research reference.